Temporary agency work in the Finnish health care sector: Greater flexibility and freedom in the workplace?. (1st July 2011) - Hannele Palukka,; Tiina Tiilikka,
Abstract : This article explores the views of temporary agency workers on their positions and roles in Finnish health care organisations. It aims to answer the question of how agency doctors and nurses perceive the content and social dimensions of agency work as well as their exercise of self-determination in agency work. The article is based on a questionnaire survey carried out in 2006, which found that agency employment in the health care sector is regarded as a flexible way of working that allows for considerable freedom. Doctors, in particular, have made the conscious choice to take up agency work, which fits in well with their personal life situations. However, there are definite limits to agency work that do not always favour the young worker or the patient. Agency employment does not provide adequate opportunities for guidance and support. Furthermore, young doctors and nurses do not have enough influence over the design of patient care. Even though flexible agency work is a voluntary choice for many health care professionals, it is necessary to ask whether it severs the connections with previous experiences and circumstances on which practical health care provision is based.